The Weighted Product Implementation In Selection of Superior Jersey Materials in Gorich Industry and Production - Fitriani, Intan Indri; Agustina, Nur Ngaenun; Fajariyanti, Alya Nur; Tahyudin, Imam (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
The success of a convection business is determined by the materials used. The more the need for orders at GORICH Industry and production convection, the business owner must be competent in producing and selecting superior materials so that customers feel satisfied with the products purchased. The number of materials and the various criteria for these materials requires a decision support system as a solution for selecting the best materials, which is used as a recommendation for material selection to prospective buyers. This method was chosen for this study using the Weighted Product method because it can determine the weight value for each attribute; in this case, it can be followed by ranking, which will be able to select each quality from the best alternative from several existing choices. From the results of the analysis, it was also found that the jersey material alternative recommended at Gorich Industry and Production fell on the A8 option, namely Emboss material.